Sistema de actividades para el fortalecimiento del proceso de enseñanza-aprendizaje de la lectoescritura - Franco Mosquera, Rosa Delia (Machala, Utmachala, 2023)
The process of teaching - learning literacy is fundamental in the social, intellectual and personal development of the human being. To teach reading and writing properly, you must have knowledge about the methodologies that allow you to develop literacy skills in children, in an active and innovative way; however, traditional methods that affect the quality of the process continue to be used. To achieve the strengthening of the teaching-learning process of literacy in the Second Grade of the Elementary Sub Level of Basic Education, in this research a Systemof activities was developed, based on the methodology of orality to writing. During the research, theoretical and empirical methods were used that made it possible to build the theoretical framework and diagnose the situation. The research was of an explanatory type, with a mixed approach, and the population was constituted by the 41 students and the two teachers of the second grade of Elementary Basic Education of the school "Rogerio Zamora Palacios". The System of activities is based on the methodology of orality to writing, and contains the theoretical and methodological foundation that guides its implementation and evaluation. The proposal was applied in the subject Language and Literature of the second grade of the Sub level of Elementary Basic Education, of the school "Rogerio Zamora Palacios". The evaluation was carried out by interpreting the data obtained in the empirical methods, after applying the System of activities; in them, the strengthening of literacy was evidenced, since all the indicators improved considerably.
El proceso de enseñanza - aprendizaje de la lectoescritura es fundamental en el desarrollo social, intelectual y personal del ser humano. Para enseñar a leer y escribir adecuadamente, se deben poseer conocimientos sobre las metodologías que permiten desarrollar habilidades lectoescritoras en los niños, de manera activa y novedosa; sin embargo, se continúan utilizando métodos tradicionales que inciden en la calidad del proceso. Para lograr el fortalecimiento del proceso de enseñanza – aprendizaje de la lectoescritura en el Segundo Grado del Sub Nivel Elemental de Educación Básica, en esta investigación se elaboró un Sistema de actividades, basado en la metodología de la oralidad a la escritura. Durante la investigación se utilizaron métodos teóricos y empíricos que posibilitaron la construcción del marco teórico y el diagnóstico de la situación. La investigación fue de tipo explicativa, con enfoque mixto, y la población estuvo constituida por los 41 estudiantes y los dos docentes de segundo grado de Educación Básica Elemental de la escuela “Rogerio Zamora Palacios”. El Sistema de actividades, se basa en la metodología de la oralidad a la escritura, y contiene la fundamentación teórica y metodológica que orienta su implementación y evaluación. La propuesta se aplicó en la asignatura Lengua y Literatura de segundo grado del Sub nivel de Educación Básica Elemental, de la escuela “Rogerio Zamora Palacios”. La evaluación se realizó mediante la interpretación de los datos obtenidos en los métodos empíricos, después de aplicado el Sistema de actividades; en ellos se evidenció el fortalecimiento de la lectoescritura, pues todos los indicadores mejoraron considerablemente.
Keywords: PROCESO DE ENSEÑANZA-APRENDIZAJE; LECTOESCRITURA; METODOLOGIA